1997
DOI: 10.1128/jcm.35.4.856-861.1997
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of four molecular typing methods for evaluating genetic diversity among Candida albicans isolates from human immunodeficiency virus-positive patients with oral candidiasis

Abstract: Candida albicans strain delineation by karyotyping, NotI restriction pattern analysis, hybridization with specific probe 27A, and PCR fingerprinting with the phage M13 core sequence were performed with 30 isolates from the oral cavities of 30 human immunodeficiency virus (HIV)-infected patients and 8 reference strains. Within the panel of clinical isolates, 20 were geographically related, although 10 isolates were susceptible to fluconazole and 10 isolates were resistant to fluconazole. The remaining isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
29
0
9

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 18 publications
3
29
0
9
Order By: Relevance
“…3). In a preliminary run, we found that the conditions used were optimal for separation of high, but not low‐molecular‐weight chromosomes as reported by previous workers (7). Thus, in order to achieve better discrimination, electrophoretic parameters were amended as described in the Methods.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…3). In a preliminary run, we found that the conditions used were optimal for separation of high, but not low‐molecular‐weight chromosomes as reported by previous workers (7). Thus, in order to achieve better discrimination, electrophoretic parameters were amended as described in the Methods.…”
Section: Resultssupporting
confidence: 76%
“…A recent study indicated genotypic clustering among FLZ‐resistant geographically related isolates from HIV‐infected patients, suggesting a common origin of the strains (9). In contrast, other workers who used four independent molecular typing methods (electrophoretic karyotyping, macrorestriction analysis of chromosomal DNA with Not I, hybridization of EcoR I‐digested DNA with the 27A repeat sequence of C. albicans, and PCR fingerprinting) were unable to demonstrate a clonal origin of the FLZ‐resistant strains amongst HIV‐positive patients (7). Therefore, the main objective of the current study was to determine whether geographically related FLZ‐resistant C. albicans isolates in a single locale have a clonal origin.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Abbreviations: AIDS, acquired immune deficiency syndrome; ALP, alkaline phosphatase; ALT, alanine aminotransferase; ANOVA, analysis of variance; AST, aspartate aminotransferase; BUN, blood Introduction Oral candidiasis, as a result of infection by the opportunistic fungus, Candida albicans, is a major cause of oral and esophageal infection in immunocompromised individuals (1,2), including up to 90% of AIDS affected patients (3). Despite excellent pharmacokinetic characteristics and low toxicity of known efficacious antifungal agents like fluconazole, treatment failures are still encountered because of the emergence of antifungalresistant C. albicans (3)(4)(5). The need to develop alternate therapeutic agents has hence soared tremendously.…”
mentioning
confidence: 99%
“…Theoretically, genotypic approaches should offer more stability and have, in practice, proven to be more discriminatory than phenotypic methods (10). Electrophoretic karyotyping (EK) involves the separation of chromosomalsized DNA molecules by pulsed-field gel electrophoresis (PFGE) and has been used successfully in candidal typing (14,15). An alternative approach is the use of polymerase chain reaction (PCR) based methods such as RAPD-PCR, amplification of hypervariable microsatellite DNA sequences and inter-repeat PCR [IR-PCR; (16,17)].…”
mentioning
confidence: 99%